2011
DOI: 10.2169/internalmedicine.50.5767
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Combination Therapy of Natural Human Interferon Beta and Ribavirin in Chronic Hepatitis C patients

Abstract: Objective The aim of this study was to evaluate the efficacy and safety of combination therapy of natural human interferon-beta and ribavirin for patients for whom prior interferon therapy was discontinued due to depression induced by interferon-alpha. Methods Inclusion criteria were as follows; 1) HCV-genotype 1b, 2) serum HCV RNA level of !100 KIU/mL, 3) stopping the prior interferon-alpha monotherapy or combination therapy of interferon-alpha and ribavirin due to the appearance of depression. A total of 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…A retrospective study of natural human IFN‐β + ribavirin combination therapy in the treatment of 40 cases with genotype 1b HCV infections reported fewer discontinuations due to adverse reactions, and only mild decreases in platelet counts . Even patients with a history of discontinuing IFN‐α therapy due to depression tolerated IFN‐β + ribavirin combination therapy well in terms of depressive symptoms and other adverse reactions . IFN therapy with natural human IFN‐β is therefore recommended in patients in whom IFN‐α therapy is not tolerated, for example, those with a history of depression.…”
Section: Interferon Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study of natural human IFN‐β + ribavirin combination therapy in the treatment of 40 cases with genotype 1b HCV infections reported fewer discontinuations due to adverse reactions, and only mild decreases in platelet counts . Even patients with a history of discontinuing IFN‐α therapy due to depression tolerated IFN‐β + ribavirin combination therapy well in terms of depressive symptoms and other adverse reactions . IFN therapy with natural human IFN‐β is therefore recommended in patients in whom IFN‐α therapy is not tolerated, for example, those with a history of depression.…”
Section: Interferon Therapymentioning
confidence: 99%
“…If the previous treatment was IFN or Peg‐IFN monotherapy, as a general rule, retreatment should be with Peg‐IFN + ribavirin combination therapy. When Peg‐IFN‐α is contraindicated due to depression or depressive symptoms, IFN‐β can be used instead of Peg‐IFN . When the previous therapy included ribavirin, telaprevir + Peg‐IFN + ribavirin combination therapy should be used.…”
Section: Interferon Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…IFN-beta was previously shown to have different signaling and biological activities from those of IFN-alpha, and achieved a higher rate of viral clearance than IFN-alpha [18][19][20][21][22][23]. The incidence of AEs such as depression, alopecia, general fatigue, and hematological changes were lower during therapies with n-IFN-beta than those with IFN-alpha [24][25][26]. In constrict to the actions of IFN-alpha, IFN-beta and IFN-lambda signaling in the liver did not become refractory during stimulation of the IFN signaling transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a patient infected with HCV genotype 1 who failed to respond to interferon with or without ribavirin seven times but then achieved a SVR using natural interferon-beta plus ribavirin for 48 wk [25] . Arase et al [42] observed that re-treatment with natural interferon-beta plus ribavirin for 48 wk led to an SVR in 38% (5/14) of previously treated-patients infected with HCV genotype 1b and a high viral load; moreover, the SVR rates were 100% (4/4) and 83% (5/6) in patients who were negative for HCV RNA at 12 wk and 24 wk, respectively (Table 1). It has recently been reported that anti-interferonalpha neutralizing antibody is associated with a non-SVR to peginterferon-alpha plus ribavirin in chronic hepatitis C patients [43] .…”
Section: Natural Interferon-beta Plus Ribavirin For Hcv-patients Prevmentioning
confidence: 99%